If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -6 = 18x + 36 Reorder the terms: -6 + 12x = 18x + 36 Reorder the terms: -6 + 12x = 36 + 18x Solving -6 + 12x = 36 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. -6 + 12x + -18x = 36 + 18x + -18x Combine like terms: 12x + -18x = -6x -6 + -6x = 36 + 18x + -18x Combine like terms: 18x + -18x = 0 -6 + -6x = 36 + 0 -6 + -6x = 36 Add '6' to each side of the equation. -6 + 6 + -6x = 36 + 6 Combine like terms: -6 + 6 = 0 0 + -6x = 36 + 6 -6x = 36 + 6 Combine like terms: 36 + 6 = 42 -6x = 42 Divide each side by '-6'. x = -7 Simplifying x = -7
| 17(4-z)+6z=-2 | | 7(3w+5)=12 | | 3x+(x+10)+90+150=720 | | 3(b-2)=2(b+3) | | x-3/5=9/10 | | 5x=84-7x | | 41=3x+4(x-2) | | 1/3(6y-3/5)=1/10 | | 2(b+6)=450 | | 5(x+4)=36 | | 160x^2+24xy-16y^2=0 | | (3+z)(3z-4)=0 | | 10t+214=240 | | 140=7x+7(x-4) | | .6q=4.50 | | 8(x+1)=5(x+4) | | 3x+5+2x-2+5x+6+4x+2+5x+x-10+2y=900 | | 2x+2(6x-10)=92 | | ln(4x)+ln(3+x)=1 | | 2f+5=45 | | 2X-18X+40=0 | | .25m=32 | | 4800/x^4=21 | | 2a*64=8*6a-4 | | -3+5x=-53 | | 3/p=5/9 | | x+7y-23=0 | | 5/s=6/29 | | n^2-12n-62=0 | | 4x-2+6x=98 | | px(x-3)+9=0 | | 44=15c-4 |